PENERAPAN MODEL COOPERATIVE LEARNING TYPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR MULTIMEDIA 3D KELAS XI JURUSAN MULTIMEDIA (MM) DI SMK NEGERI 2 PADANG PANJANG - Ceci Fenesa; Efrizon Efrizon; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
Problems in this study is the lack of achievement of the target of Completeness Minimum Criteria (KKM) the study of students in the subject of Multimedia 3 Dimention. This study aimed to see whether there is any difference in learning outcomes using Model Cooperative Learning Type Group Investigation by learning outcomes that do not use the Model Cooperative Learning Type Group Investigation, which is Direct Instruction. This research is experimental research, this study population was a class XI MM student of SMK Negeri 2 Padang Panjang Academic Year 2014/2015. This research is a quasi experimental. The sampling technique was performed using purposive sampling technique. Experimental class is a class that is treated by using a Model Cooperative Learning type Group Investigation and the control class is the class that uses the Direct Instruction model. Data were collected from the test results in the form of learning objective about a total of 33 items. Data were analyzed manually to normality test, homogeneity, and hypothesis testing. The study of the test results can be the average value of student learning outcomes using Model Cooperative Learning Type Group Investigation is 83.63 while the average value of students who use the Direct Instruction models lower at 74.45 with the percentage difference between classroom learning outcomes experimental and control class is 12.32%. The average value obtained posttest experimental class of 78.4 and an average value of 72.2 posttest control class. The result of t testing showed that the score of  tcounting > ttable (1.962 > 1.672), so that the working hypothesis (H1) is accepted or rejected the null hypothesis (Ho). This means that significantly increase learning outcomes experimental class is greater than the control class learning outcomes.  Key-word : Cooperative Learning Group Investigation, Learning Model, Direct Instruction, Learning Outcomes, Control and Experiment, Multimedia 3 Dimention.